2006
DOI: 10.14411/fp.2006.022
|View full text |Cite
|
Sign up to set email alerts
|

Sand fly saliva: effects on host immune response and Leishmania transmission

Abstract: Abstract. The feeding success of sand flies (Diptera: Phlebotominae) is linked to the vast array of pharmacological substances in their saliva, which interferes with the host haemostasis and immune response. Modification of feeding site plays also an important role in Leishmania transmission. In naive hosts, co-inoculation of saliva and Leishmania parasites increases the chance of successful transmission. Disease exacerbation seems to be associated with enhanced production of type 2 cytokines and selective inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 74 publications
0
61
0
1
Order By: Relevance
“…Notably, the plasmids that were not immunogenic in hamsters were able to produce a cellular or antibody response in mice (data not shown). This finding suggests that the absence of an immune response to some of these plasmids in hamsters may be caused by host specificity (9). However, we cannot exclude a dose-related effect caused by differential expression of plasmids after hamster immunizations.…”
Section: Screening Of Lu Longipalpis Sand Fly Salivary Proteins For mentioning
confidence: 86%
See 1 more Smart Citation
“…Notably, the plasmids that were not immunogenic in hamsters were able to produce a cellular or antibody response in mice (data not shown). This finding suggests that the absence of an immune response to some of these plasmids in hamsters may be caused by host specificity (9). However, we cannot exclude a dose-related effect caused by differential expression of plasmids after hamster immunizations.…”
Section: Screening Of Lu Longipalpis Sand Fly Salivary Proteins For mentioning
confidence: 86%
“…Saliva contains a variety of potent and pharmacologically active components that favorably change the environment at the feeding site (4-7). Exposure to sand fly bites or salivary proteins results in strong cellular and/or humoral immunity specific to these components (8)(9)(10)(11). In animal models of CL, mice immunized with Phlebotomus papatasi salivary gland homogenate (SGH) or preexposed to uninfected sand fly bites were protected against Leishmania major infection delivered via needle inoculation (2) or by infected sand flies (12).…”
mentioning
confidence: 99%
“…This saliva is known to contain a variety of anti-hemostatic, vasodilatory, and immunomodulatory compounds 13. Therefore, saliva will always be present during a bite from either an uninfected or infected sand fly.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms and determinants of clinical severity and pathogenicity are not fully understood and might be determined by factors related to the parasite (Banuls et al, 2011; Stuart et al, 2008), the vector (Murray et al, 2005; Rohousova and Volf, 2006) and the host genetic background and immune responses (Kane and Mosser, 2000; Sakthianandeswaren et al, 2009; Schriefer et al, 2008). In Tunisia, a couple of studies showed that various L. major isolates differ in their experimental pathogenicity when injected into the footpad of the genetically susceptible BALB/c mice (Kebaier et al, 2001 and Attia, unpublished data).…”
Section: Introductionmentioning
confidence: 99%